Lost in translation? Polycentricity and the mutation of concepts across fields. Issue 4 (4th July 2021) - Savage, Glenn C.; Dang, Thi Kim Anh
ABSTRACT: This paper explores the emergence of the term 'polycentricity' in education policy research and compares its use in education to its historical use in its 'parent fields' of political science and economics. We focus on the leading role of Stephen Ball and colleagues in popularising the term in education, inspiring other education scholars to harness the term to examine contemporary governance arrangements. Our primary argument is that in broad descriptive terms, the use of the term in education generally mirrors its use in political science and economics. Its prescriptive usage, however, is very different, with arguments about the impacts of polycentricity in education policy often contrasting sharply with arguments in political science and economics. This has resulted, we argue, in core elements of the concept being 'lost in translation'. Yet, at the same time, its use in education has also generated new and important critical insights.